Impact of land reclaimation. Study area: Macallum Street Ghaut, Penang / Noraini Jaafar - Jaafar, Noraini (Faculty of Architecture, Planning & Surveying, 1984)
Coastal development should not only take into consideration the economic benefits but also the environment effect. The coastal land reclaimation in Macallum Street Ghaut, Penang, in its eagerness to win land from the sea has had many adverse impact on the physical, social economic as well as biological environment. The adverse impact can be seen in form of high construction costs, loss of income to those who rely on the aquatic habitats for their living and also to the environmental pollution and traffic hazards as revealed in the survey.